Fates of Rare Species under Siege from Invasion: Persistence of Coccinella novemnotata Herbst in Western North America alongside an Invasive Congener - Evans, Edward W. (Frontiers in Ecology and Evolution, 2017)
Species invading new geographic regions may threaten continued existence of similar, indigenous relatives, particularly those species whose rarity may reflect an already tenuous existence. The spectacular colonization of North America in recent decades by Coccinella septempunctata L. has generated widespread concern over potentially adverse effects on population viability of native species of ladybird beetles (Coccinellidae). Coccinella novemnotata Herbst in particular has been hypothesized to be at great risk, as this species apparently dwindled in numbers across much of North America during the twentieth century. Here results of sampling diverse habitats over three decades are examined to address the fate of C. novemnotata in the intermountain region of western North America following the establishment of C. septempunctata during the 1990s. Alfalfa fields have served as a major habitat for C. novemnotata in the intermountain west. Sweep sampling in the late 1980s and early 1990s demonstated that C. novemnotata and C. septempunctata were both rare members of the alfalfa lady beetle community. Subsequent sampling in alfalfa over the next two decades revealed that populations of C. septempunctata increased greatly, while populations of C. novemnotata remained low but persistent. Similarly, modest numbers of C. novemnotata were found continuing to persist, often alongside large numbers of C. septempunctata, in a variety of other habitats, including sagebrush steppe and weed-infested rangeland and riparian sites. Morphological comparison of these individuals of C. novemnotata with museum specimens collected throughout the twentieth century revealed no significant difference in mean body size between these recently and previously collected individuals, nor any significant long-term decrease in body size following the arrival of C. septempunctata, as might reflect increasing food limitation for larval C. novemnotata. Collectively these results indicate that even in the face of invasion by a dominant competitor, C. novemnotata has maintained an ecological foothold in the intermountain west of North America, occurring in diverse habitats including both those supporting low and high numbers of the invader. The availability of these diverse habitats across a heterogeneous landscape may promote persistence less tenuous, even as confronted with invasion, than the low abundance of C. novemnotata alone might suggest.